A Comparative Study of AlCl3 and FeCl2-Modified TiCl4/MgCl2/THF Catalytic System in the Presence of Hydrogen for Ethylene Polymerization. (6th September 2016) - Niyomthai, Thanyathorn; Ratchadaphet, Aniroot; Jongsomjit, Bunjerd; Praserthdam, Piyasan
Abstract : Ethylene homopolymerization over TiCl4 /MgCl2 /THF catalysts modified with different metal halide additives (AlCl3 and FeCl2 ) with and without hydrogen was investigated based on catalytic activity and polymer properties. Lewis acid modification can improve activity because it can remove the remaining THF in the final catalyst, which can poison the catalyst active sites via the ring-opening of THF that was confirmed by XRD measurements. Moreover, the activity enhancement was due to the formation of acidic sites by modifying the catalysts with Lewis acids. Thus, FeCl2 doped catalyst (Fe-THF) exhibited the highest activity followed by AlCl3 doped catalyst (Al-THF) and undoped catalyst (None-THF). In H2 /C2 H4 molar ratio of 0.08, Fe-THF showed a better hydrogen response than Al-THF due to more titanium cluster distribution. Fe-THF is considered to have more clustered Ti species than Al-THF. As a consequence, it led us to obtain more possible chances to precede chain transfer reaction by hydrogen. The molecular weight, melting temperature, and crystallinity of obtained polymers were investigated by GPC and DSC measurement, respectively.